Kim jest postmodernistyczny "homo oeconomicus", czyli pytanie o współczesne relacje pomiędzy rodziną a rynkiem - Michalski, Michał Adam (Annales. Etyka w Życiu Gospodarczym, 2011)
This article undertakes the question of „economic man” in context of postmodern philosophy. The purpose of it is to analyze current understanding of man in market surrounding and his family relations. In the beginning the genesis of homo economicus model is presented and attempt is made to find answer to the question of its contemporary meaning and “family situation”. Then the article shows why we should resign from using this model and substitute it with homo socioeconomicus. The very concept of homo economicus – well known and often discussed – although reduces human being, in the light of postmodern thinking seems to relive. That is why it is necessary to reflect if there is similarity between “economic man” and the vision of man preferred by postmodernism. One of the proofs for it may be current situation of family which is not supported by postmodern homo economicus concept. It seems to be logical consequence when we realize that individualism of “economic man” is strengthened by postmodern antipathy towards social institutions.